PROFESSIONAL SELF-DETERMINATION OF HIGHER SCHOOL STUDENTS - Koryakovtseva, Olga; Bugaychuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is devoted to the problem of professional self-determination, which is urgent for today's youth. The role of professional choice in a person's life is great, and the possibilities with which a young man approaches this process plays a decisive role. In their article, the authors present the results of an empirical study of thepersonal characteristics of students in grades 9, 10, 11 and their readiness to choose a profession. We identified important and significant connections between the level of development of self-esteem and reflexivity with such indicators of professional self-determination as autonomy and emotional attitude. This result indicates that the level of development of his self-awareness plays a decisive role in the professional self-determination of a young man. It is the teacher's task to help high school students in professional self-determination.